2013
DOI: 10.1002/hep.26509
|View full text |Cite
|
Sign up to set email alerts
|

Diastolic dysfunction is a predictor of poor outcomes in patients with cirrhosis, portal hypertension, and a normal creatinine

Abstract: We investigated left ventricular diastolic dysfunction (LVDD) and its relationship with circulatory function and prognosis in cirrhosis with portal hypertension and normal creatinine. Conventional and tissue Doppler (TDI) echocardiography, systemic and hepatic hemodynamics, and the activity of endogenous vasoactive systems (AEVS) were measured prospectively in 80 patients. Plasma renin activity (PRA; >4 ng/mL/hour) was used as a surrogate of effective arterial blood volume. Patients were followed up for 12 mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

20
162
3
10

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 147 publications
(195 citation statements)
references
References 38 publications
20
162
3
10
Order By: Relevance
“…As in the present study by Karagiannakis et al, several studies have reported a direct relation to prognosis, whereas other studies have failed to do so [6,8,14]. In a recent study by Ruiz-del-Arbol et al [8], the authors reported a direct relationship between variables obtained from tissue Doppler imaging (E/e 0 ) ratio and prognosis. In patients undergoing invasive procedures such as insertion of a transjugular intrahepatic porto systemic shunt (TIPS), the presence of diastolic dysfunction has been shown to predict survival [9].…”
supporting
confidence: 57%
See 4 more Smart Citations
“…As in the present study by Karagiannakis et al, several studies have reported a direct relation to prognosis, whereas other studies have failed to do so [6,8,14]. In a recent study by Ruiz-del-Arbol et al [8], the authors reported a direct relationship between variables obtained from tissue Doppler imaging (E/e 0 ) ratio and prognosis. In patients undergoing invasive procedures such as insertion of a transjugular intrahepatic porto systemic shunt (TIPS), the presence of diastolic dysfunction has been shown to predict survival [9].…”
supporting
confidence: 57%
“…This condition has been termed cirrhotic cardiomyopathy, which designates a cardiac dysfunction that includes impaired cardiac contractility with systolic and diastolic dysfunction and electromechanical abnormalities in the absence of other known causes of cardiac disease [4]. Cirrhotic cardiomyopathy can be demasked by physical or pharmacological stress, which may reveal in particular a systolic dysfunction, which seems to contribute to several cirrhotic complications such as the formation of ascites [5,6] and the development of hepatic nephropathy [7,8]. Additionally, cirrhotic cardiomyopathy seems associated with the development of heart failure in relation to invasive procedures such as shunt insertion and liver transplantation [9,10].…”
mentioning
confidence: 99%
See 3 more Smart Citations